Psikologi Positif Membangun kebahagiaan dan kesejahteraan mental: Psikologi positif - indi, rovida (Maliki Interdisciplinary Journal, 2025)
Positive psychology is a field of study that focuses on developing the good side of humans and also improving the quality of life through useful mental strategies. This article will discuss the basic concepts of positive psychology, ways to build happiness and mental well-being, as well as the implications in everyday life. The author will explain how mindfulness, self-awareness, and social support techniques can increase a person’s level of happiness. Apart from that, this article will also provide practical examples of the implementation of positive psychology in real situations. Furthermore, positive psychology not only emphasizes improving psychological problems, but also strengthening one’s potential and achieving a meaningful life. This approach helps individuals to focus more on their strengths, develop a sense of gratitude, and build an optimistic mindset in facing life’s challenges. Thus, positive psychology can be an important guide in forming individuals who are resilient, have healthy social relationships, and are able to achieve balance between personal and professional life.